Analisis Komparatif NetSpot dan Ekahau Dalam Optimalisasi Penempatan Access Point di DISDIKPORA Kabupaten Buleleng - Darma Putra Purba; Gede Arna Jude Saskara; Bagus Gede Krishna Yudistira (POLITEKNIK NEGERI JAKARTA, 2025)
Optimal access point (AP) placement is essential to ensure uniform and high-quality WiFi signal coverage, particularly in government institutions such as the Department of Education, Youth, and Sports (DISDIKPORA) of Buleleng Regency. This study aims to analyze and compare the effectiveness of Ekahau AI Pro and NetSpot applications in optimizing AP placement. The research methodology integrates Comparative Analysis, Action Research, and Benchmarking, following a structured process consisting of diagnosis, action planning, action taking, evaluation, and learning. Measurements were conducted through active and passive surveys, with cross-validation performed using WiFi Analyzer as a reference tool. Data were collected based on key parameters: Received Signal Strength Indicator (RSSI), blank spot detection, result consistency, and time efficiency. The results indicate that both applications accurately detected all blank spots. However, Ekahau AI Pro demonstrated higher consistency, with only a 1.5 dBm deviation, making it well-suited for long-term planning in complex building environments, despite requiring more time and higher costs. In contrast, NetSpot delivered sufficiently accurate results with an average difference of 6.75 dBm and significantly faster execution time, making it ideal for rapid network audits under limited budgets. Based on the findings, Ekahau AI Pro is recommended for complex environments demanding high accuracy, while NetSpot is more appropriate for fast, dynamic, and cost-effective assessments. This study provides technical recommendations for WiFi network optimization at DISDIKPORA and offers strategic guidance for selecting suitable network mapping tools in similar organizations.